دور الرقابة الشرعية في تطوير العمل المصرفي الإسلامي في الجزائر - اسحاق حشيفة; لخضر شبرو; معمري عبد الحميد (university of eloued جامعة الوادي, 2025)
تتناول مذكرة "دور الرقابة الشرعية في تطوير العمل المصرفي الإسلامي في الجزائر" الإشكالية المتعلقة بكيفية تعزيز دور الرقابة الشرعية في المؤسسات المصرفية الإسلامية. تفترض الدراسة أن الرقابة الشرعية تؤثر إيجابيًا على كفاءة العمليات المصرفية، وتساهم في تقليل المخاطر المالية والقانونية. النتائج تشير إلى أن وجود هيئة رقابة نشطة يقلل الأخطاء ويُسَرّع الإجراءات التمويلية، كما أثبتت تجارب بنك المعاملات الإندونيسي زيادة مؤشرات الأداء بعد تفعيل الرقابة الشرعية. علاوة على ذلك، يقلل تطبيق الفتوى الشرعية من التعرض للعقوبات التنظيمية، كما ساهمت الرقابة المُشددة في مصرف الراجحي في خفض التمويل غير المتوافق، وتظهر الدراسة علاقة طردية بين مستوى تنفيذ الرقابة الشرعية ومدى التزام البنوك الإسلامية بمبادئ الشريعة، حيث أظهرت البنوك التي منحت هيئاتها سلطة تصحيحية كاملة درجة أعلى من الالتزام. كما توفر الرقابة الشرعية بدائل جديدة مثل المرابحة الإلكترونية وصكوك إقراض متناهي الصغر، مما يساهم في الابتكار المالي. من الضروري أيضًا أن تتمتع الهيئة بالاستقلالية الإدارية والمالية لضمان نزاهة الفتوى وموضوعية التدقيق، حيث أن غياب الاستقلالية قد يؤدي إلى تراجع ثقة العملاء. وأخيرًا، يشير التقرير إلى نقص الكوادر المؤهلة في فقه المعاملات الإسلامية كعائق أمام فعالية الهيئة، مما يستدعي إعداد برامج تدريبية متخصصة. The memorandum "The Role of Sharia Compliance in Developing Islamic Banking in Algeria" addresses the issue of how to enhance the role of Sharia compliance in Islamic banking institutions. The study assumes that Sharia compliance positively affects the efficiency of banking operations and contributes to reducing financial and legal risks. The results indicate that the presence of an active Sharia supervisory board reduces errors and accelerates financing processes. Additionally, experiences from the Indonesian banking sector have shown an increase in performance indicators following the activation of Sharia compliance. Moreover, the application of prior Sharia rulings minimizes exposure to regulatory penalties, while strict oversight at Al-Rajhi Bank has contributed to reducing non-compliant financing. The study demonstrates a direct relationship between the level of Sharia compliance implementation and the adherence of Islamic banks to Sharia principles, as banks that granted their boards full corrective authority exhibited a higher degree of commitment. Sharia compliance also provides new alternatives such as electronic Murabaha and micro-lending Sukuk, contributing to financial innovation. It is also essential for the board to have administrative and financial independence to ensure the integrity of rulings and the objectivity of audits, as a lack of independence may lead to a decline in customer trust. Finally, the report highlights the shortage of qualified personnel in Islamic transaction jurisprudence as an obstacle to the effectiveness of the board, necessitating the development of specialized training programs.
Keywords: الرقابة الشرعية; العمل المصرفي الإسلامي; بنك المعاملات; بنك الراجحي; بنك البركة; Sharia Compliance - Islamic Banking - Transactional Banks - Al-Rajhi Bank - Baraka Bank